An inquiry into the structure and function of space in indigenous settlement in Ovamboland - Mills, Glen Trevor (School of Architecture, Planning and Geomatics, 2020)
The problem of informing appropriate architectural practice in southern Africa is addressed by proposing to divert analytical attention away from the level of appearances when researching the form of indigenous settlement patterns and architecture. By way of example, an empirical study of the homestead as a unit of settlement pattern in Ovamboland is undertaken by exploring the ways in which the designer/builders themselves perceive and value space with a view to identifying and describing the organizational structure of the homestead. The initial assumption is that this form of settlement, examined as a set of spatial relations, encodes within its organizational structure the formula (or diagram) for its reproduction. The hypothesis is that a relevant understanding of indigenous settlement and architecture can only be grasped if inquiry extends beyond the formal aspects of style and technology to include an analysis of its spatial characteristic; this being the external projection of the socio-economic pattern (or ideology) of the people that produce it. And, such analysis being useful in identifying the formula which, when it interacts with its context, reproduces the observed settlement form. In view of this, a method of study is proposed which attempts to describe and examine settlement space from 'within' by exploring all the physical and non-physical determinants of form. This is done by isolating each determinant as a specification of settlement from and thereby arranging it into a scheme based on the scale of space with which it deals. The conclusions are, firstly, that because the homesteads display similar features of layout and accommodation there must exist a common, agreed-upon diagram which ensures its constant reproduction. Secondly, the evidence for the diagram must lie within the way the designer/builders perceive homestead space. Thirdly, this perception has its roots in historically inherited and functionally derived values and uses of space. Finally, a preliminary diagram is proposed which, it is argued, needs to be verified by undertaking further investigations of a similar nature in other areas of southern Africa where indigenous people occupy space.